2021
DOI: 10.1097/hjh.0000000000002840
|View full text |Cite
|
Sign up to set email alerts
|

The complex interaction between vitamin D, folate, and heavy metals: potential for attenuation of blood pressure effects

Abstract: consuming high sodium in their diets (>5 g/day of sodium) to moderate levels (3 to 5 g/day).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Besides its well-known role in calcium homeostasis, Vitamin D deficiency also contributes to CVD [ 13 ]. A new study revealed that the complicated relationship between vitamin D, folate, and heavy metals may be able to lessen the impact on blood pressure [ 14 ]. It is not known in the United States (U.S.) general population whether serum 25-hydroxyvitamin D (25(OH)D) levels are related to heavy metal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its well-known role in calcium homeostasis, Vitamin D deficiency also contributes to CVD [ 13 ]. A new study revealed that the complicated relationship between vitamin D, folate, and heavy metals may be able to lessen the impact on blood pressure [ 14 ]. It is not known in the United States (U.S.) general population whether serum 25-hydroxyvitamin D (25(OH)D) levels are related to heavy metal exposure.…”
Section: Introductionmentioning
confidence: 99%